On the streaming potential arising from flows having axial symmetry and the determination of zeta potential therefrom. (August 2016) - Sides, Paul J.; Prieve, Dennis C.
Abstract: Determining the zeta potential of macroscopic surfaces helps predict the surfaces' attractiveness to charged particles or cells, or tells whether the surface is clean or contaminated, among other applications. Typically, one pumps the test solution through a narrow channel formed by the test surface and measures the streaming current or streaming potential engendered thereby. It is worth considering alternative geometries: 1. The "spincoat" design, in which the test liquid is directed as a narrow jet to the axis of a disk-shaped sample rotating on its axis, offers a large signal with a small liquid flow rate, e.g. 1 mL/min. The validity of assumptions underlying the simplest analysis of this design improves as the flow rate decreases at constant rotation rate. 2. The "rotating disk", in which the sample is spun on its axis while immersed in solution, offers much reduced surface conductance and uniform accessibility to charged entities in solution. This design also provides a means for determining the zeta potential of open porous structures without requiring compression of the sample into a plug. 3. The "impinging jet, " in which a jet of liquid is directed to a nonrotating sample, allows an arbitrary sample shape and detection of spatial variations of zeta potential. Deceleration of the radially expanding film causes a "hydraulic jump instability" some distance from the axis; the radius of the jump defines the probed area. Graphical abstract: Highlights: Directing a narrow jet to a rotating sample generates a large streaming potential. The "rotating disk" offers uniform accessibility to charged entities in solution. Rotating porous samples give large streaming potentials with no compression needed. An impinging jet generates streaming potential on planar samples. A hydraulic jump defines the region of the sample generating streaming potential.